Volumetric Properties of Binary Mixtures of n-Butylacetate with 1-Butanol, 2-Butanol, 1,2-Butanediol and 1,3-Butanediol at Different Temperatures - REZAEI SAMETI, M.; ILOUKHANI, H.; RAKHSHI, M. (Asian Journal of Chemistry, 2010)
Densities for binary mixtures formed by n-butylacetate with 1-butanol, 2-butanol, 1,2-butanediol and 1,3-butanediol have been determined over the full range of compositions in the temperature range 298.15 to 308.15 K at the ambient pressure 81.5 kPa, using an Anton Paar DMA 4500 oscillating density meter. The excess molar volumes (Vm E), excess partial molar volumes (Vi E), were calculated from experimental densities. The excess molar volumes for all binary mixtures positive and increase with increasing temperatures from 298.15 to 308.15 K. This means that the interaction of like moleculars is stronger than the unlike molecular intractions. The binary data of Vm E were correlated as a function of the mole fraction by using the Redlich-Kister type function to determine the fitting parameters and the standard deviations. The experimental data of the constituent binaries are analyzed to discuss the nature and strength of intermolecular intractions in these mixtures.